NCOG-42. THE IMPACT OF PER2 POLYMORPHISMS ON THE EXPRESSION OF SLEEP AND ACTIVITY IN A NOVEL MOUSE MODEL OF CRANIAL-IRRADIATION-INDUCED HYPERSOMNOLENCE (C-RIH). (14th November 2022) - Adegbesan, Kendra; Ardori, Francesco Tomassoni; Yanpallewar, Sudhirkumar; Briceno, Nicole; King, Amanda; Tessarollo, Lino; Gilbert, Mark; Smart, DeeDee; Armstrong, Terri; Shuboni-Mulligan, Dorela
Abstract: Chronic daytime sleepiness, or hypersomnolence, is one of the most common and disruptive side effects of cranial radiotherapy and is associated with disturbances in mood and cognition in primary brain tumor patients. Our laboratory previously found that increased minor allele presence of the PERIOD2 (PER2) polymorphism (rs934945, G-E mutation) correlated with a decreased likelihood of hypersomnolence in PBT patients. PER2, a key molecular component of the circadian clock, assists in the generation and maintenance of daily sleep/wake rhythms. We aim to understand the effects of this PER2 polymorphism on radiation sensitivity within our previously established mouse model of cranial-irradiation-induced hypersomnolence (C-RIH). Five cohorts of male/female transgenic mice were generated using CRISPR-Cas9, replacing the endogenous mouse CRY binding domain with one of two polymorphic variants within the human genome (G-E and conventional Per2h23). General activity and sleep were monitored continuously over 10 days before and after therapeutic irradiation (whole brain, 15Gy, single fraction). Independent samples t-tests compared knock-in groups and species variants. During the active phase, G-E knock-in mice showed less radiation-induced suppression of activity (-7% males; -20% females) relative to Per2h23 knock-ins (-18% males; -36% females). For rest, both male and female G-E mice (+4% males; +16.4% females) expressed less radiation induced sleep during their active phase than Per2h23 mice (+7% males; +27.7% females). However, this pattern did not rise to significance. Current experiments will expand the numbers of mice used in each group to further explore these initial patterns. Understanding the genetic markers that predict radiation sensitivity could help generate more patient specific methods to mitigate these negative behavioral outcomes. Our mouse models provide a platform to introduce polymorphisms and test their impact on treatment-related symptoms.